Data for dielectric surface passivation for silicon solar cells: A review - Bonilla, RS; Wilshaw, P; Hamer, P (University of Oxford, 2017)
Embedded Matlab raw data on effective lifetime, surface recombination velocity, implied open circuit voltage, and recombination current density for different passivation dielectrics.